Differential Plasma Protein Regulation and Statin Effects in Human Immunodeficiency Virus (HIV)-Infected and Non-HIV-Infected Patients Utilizing a Proteomics Approach. (20th April 2020) - deFilippi, Chris; Toribio, Mabel; Wong, Lai Ping; Sadreyev, Ruslan; Grundberg, Ida; Fitch, Kathleen V; Zanni, Markella V; Lo, Janet; Sponseller, Craig A; Sprecher, Emmett; Rashidi, Narges; Thompson, Melanie A; et al.
Abstract: Background: People with human immunodeficiency virus (PWH) demonstrate increased atherosclerotic cardiovascular disease (ASCVD). Statins are being studied to prevent ASCVD in human immunodeficiency virus (HIV), but little is known regarding the effects of statins on a broad range of inflammatory and cardiovascular proteins in this population. Methods: We used a highly specific discovery proteomic approach (Protein Extension Assay), to determine statin effects on over 350 plasma proteins in relevant ASCVD pathways among HIV and non-HIV groups. Responses to pitavastatin calcium were assessed in 89 PWH in the INTREPID trial and 46 non-HIV participants with features of central adiposity and insulin resistance. History of cardiovascular disease was exclusionary for both studies. Results: Among participants with HIV, PCOLCE (enzymatic cleavage of type I procollagen) significantly increased after pitavastatin therapy and PLA2G7 (systemic marker of arterial inflammation) decreased. Among participants without HIV, integrin subunit alpha M (integrin adhesive function) and defensin alpha-1 (neutrophil function) increased after pitavastatin therapy and PLA2G7 decreased. At baseline, comparing participants with and without HIV, differentially expressed proteins included proteins involved in platelet and endothelial function and immune activation. Conclusions: Pitavastatin affected proteins important to platelet and endothelial function and immune activation, and effects differed to a degree within PWH and participants without HIV. Abstract : We assessed the effects of pitavastatin on a broad array of proteins using a highly specific proximity extension assay (PEA) in HIV and metabolic syndrome non-HIV patients. Our results highlight effects on key inflammatory, collagen, neutrophil, and integrin functions.